2008
DOI: 10.1016/j.jjcc.2008.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Plasma brain natriuretic peptide concentrations and the risk of cardiovascular events and death in general practice

Abstract: In general practice, BNP levels predicted the risk of cardiovascular events other than coronary heart disease events and of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
(42 reference statements)
3
16
0
2
Order By: Relevance
“…9 Another clinical observational study in Japan also revealed a significant influence of elevated BNP levels on CVD events, but this association was not observed for coronary heart disease. 22 The present study confirmed the results from the prior studies and provided more detailed information regarding the risks of various CVDs, including coronary heart disease and stroke. To the best of our knowledge, this is the first report to show that elevated NT-proBNP levels are an independent risk factor for the occurrence of intracerebral hemorrhage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…9 Another clinical observational study in Japan also revealed a significant influence of elevated BNP levels on CVD events, but this association was not observed for coronary heart disease. 22 The present study confirmed the results from the prior studies and provided more detailed information regarding the risks of various CVDs, including coronary heart disease and stroke. To the best of our knowledge, this is the first report to show that elevated NT-proBNP levels are an independent risk factor for the occurrence of intracerebral hemorrhage.…”
Section: Discussionsupporting
confidence: 90%
“…6,7,9,11 However, very few prospective studies have provided evidence of associations between the natriuretic peptide levels and CVD in Asian populations. 9,22 One cohort study of a Japanese population showed an association between increased BNP levels and the risk of developing ischemic stroke. 9 Another clinical observational study in Japan also revealed a significant influence of elevated BNP levels on CVD events, but this association was not observed for coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three studies were based in Europe, 8 -28,46,47 5 in North America, 29 -33 1 in Australia and New Zealand, 34 and 7 in East Asia [35][36][37][38][39][40]45 (predominantly in Japan), and 4 were multinational. [41][42][43][44] Thirty-six studies were prospective cohorts and 4 "nested" case-control studies; 14 studies recruited participants from population registers (such as general practitioners' lists or electoral rolls), and 26 were hospital based (of which 10 were clinical trials).…”
Section: Resultsmentioning
confidence: 99%
“…BNP on admission was higher in patients than in controls (25 vs 13 pg/ml, p=0.01) and it decreased to 16 pg/ml pre-discharge (p=0.0002). Another study in patients with septic shock, demonstrated that both BNP and ANP peaked on day 2 (BNP, 987 ± 160 pg/ml; ANP, 103 ± 17 pg/ml) (control group: BNP, 7 ± 0.3 pg/ml; ANP, 13 ± 1 pg/ml) [79].…”
Section: Plasma Levels Of Natriuretic Peptides In Septic Patientsmentioning
confidence: 99%